Main problems fourth year students of the B.A. in English: emphasis in teaching have when applying certain grammatical structures in written English semester (II-2016 – I-2017) Foreign Language Department–UES - Maldonado Mancía, Balmore Bladimir; Navas Solis, Iliana Noemy (2024)
Nowadays, it is important to be proficient in writing whether it is done in the mother tongue or in a foreign or a second language. Being proficient in writing can represent a great advantage to anyone who has mastered that ability. Nowadays writing is a skill demanded in almost any job or academic field. For instance, when applying for a job or a scholarship, the ones who have a better chance to get what they are applying for are those who master that ability in whatever language they write. Writing proficiently in English as a Second or foreign language is very important. When learning a new language, there are going to be many obstacles the students will need to overcome; among those ones, there can be mentioned the mastering of writing and all what it implies including a good grammar. The FLD of the University of El Salvador prepares students to become English teachers who can work in different institutions in the country or abroad. It is known that an English teacher has to be able not only to communicate in English fluently, clearly and proficiently but also to know about the language, its grammar. Therefore, if students at the FLD study to become teachers, it is expected that those students after having studied the English major for four or five years, they should not make as many grammatical errors when writing as they make, especially if they are going to be teaching the language soon.